Clinical and electrophysiological features of adult patients with combined central and peripheral demyelination- a systematic review - Andrusiów, Szymon; Dziadkowiak, Edyta; Koszewicz, Magdalena (Frontiers in Immunology, 2025)
BackgroundThe classification of combined central and peripheral demyelination (CCPD) is challenging due to unclear pathomechanisms and a lack of diagnostic and therapeutic criteria. Existing clinical data are limited to case reports or small series, with few attempts to define CCPD using radiological or molecular markers. Differential diagnosis depends on excluding well-characterized demyelinating diseases of the central and peripheral nervous systems. No systematic review has yet summarized the clinical, radiological, electrophysiological, molecular, and therapeutic evidence for CCPD.MethodsThis review follows PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, uses the JBI critical appraisal tool for case series and is registered at PROSPERO (CRD42025640575). A systematic search of Embase, MEDLINE, Web of Science, and Google Scholar was conducted for studies available up to December 2024. Inclusion criteria focused on adult patients with electrophysiological and imaging findings. Exclusion criteria included CCPD associated with infections, rheumatological conditions, or anti-MOG/anti-AQP4 antibodies.ResultsMost patients exhibited hemiparesis assessed by MMT and MRC scales, with tetraparesis often asymmetrical. Imaging revealed either diffuse CNS involvement (cerebral hemispheres, brainstem, spinal cord) or lesions limited to one or two sites. Nerve conduction studies showed primarily demyelinating features. Treatment frequently involved combination therapies.ConclusionsThis review underscores the dearth of high-quality data on CCPD, with extant studies frequently exhibiting a paucity of methodology for definitive analysis. The presence of elevated protein concentrations in CSF and the presence of antibodies, specifically anti-LacCer and anti-NF, has been identified as potential biomarkers of the disease. Furthermore, GCS in high doses might be one of the most effective treatment options.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025640575, identifier CRD42025640575.